Prevalence and Risk Factors of Senile Cataract in Balinese Population Age 50 Years Old or Older - Anak Agung Mas Putrawati Triningrat; Putu Adhi Surya Pradana; Ariesanti Tri Handayani; Gde Ngurah Indraguna Pinatih; Made Agus Kusumadjaja; Wayan Gede Jayanegara (Journal of Global Pharma Technology, 2018)
Objective: Cataract is the leading cause of blindness in the world with increasing trend both in prevalence and incidence. Surgery is the only definitive treatment for cataract but often unaffordable for society in developing countries. The incidence of cataract could be prevented by understanding its risk factors and formulate health programs according to them. The purpose of this study was to assess the prevalence and risk factors of senile cataract among 50 years old or older Balinese population. Method: The population-based cross-sectional study was conducted from September 2015 until July 2016 in Bali province. The variable’s data were obtained through direct examination and interview. Poisson regression analysis was used to assess the definitive correlation between risk factors and cataract. A p-value <0.05 or value which falls within 95% confidence interval were considered significant. Result: 550 subjects were enrolled during the study. The number of cataracts found in this study was 231 (42%). According to the analyses, cataract was significantly associated with older age (PR: 3.05; p=0.001), low educational level (PR: 2.18; p=0.04), diabetes (PR: 2.96; p=0.001), and the rate of ultraviolet exposure (PR: 1.92; p=0,002). Conclusion: The prevalence of cataract among 50 years old or older in Balinese population was 42%. Older age, low education, diabetes mellitus, and ultraviolet exposure were found to be significant and independent risk factors for cataract in 50 years old or older Balinese population.Keywords: Cataract, Prevalence, Risk factor.